Futures of work and skills: some foresight exercises in Europe and USA - Paulos, Margarida Ramires (2009)
The Knowledge-based society brought a new way of living and working. The increasing decline of work in primary sector and traditional industries, related with the significant increase of employment in the service sector and in the knowledge work, changed the way companies and individuals establish their relations, the way work and life is organised. These changes are usual and fast and so the feeling of insecurity and unpredictability become more and more sharp. In this context, foresight exercises are necessary tools helping in the identification of the key variables and main trends of evolution. This report will present some foresight studies about work and skills in Europe and USA, in order to contribute to think about possible evolutions and trends.